Impact of a community‐acquired pneumonia care bundle in North East England from 2014 to 2017—A quality improvement project. (4th October 2020) - Morrow, Gerry; Roberts, Anthony; Newton, Julia; Rees, Jon; Walkley, Michael; Flavell, Linda
Abstract: Objectives: To explore the impact of implementation of Community‐Acquired Pneumonia (CAP) quality care bundle. Setting: Eight acute hospitals in the North East of England and North Cumbria. Participants: ICD‐10 coded CAP aged >18 were identified. A total of 16 201 CAP patients were discharged 2016/2017 (15 707; 2015/2016 and 10 733; 2014/2015). Outcome measures: Secondary User Service (SUS) data were collected monthly from April 2014 to 2017. Data were pseudonymised and data flows governed by Data Sharing Agreements. CAP measures were based on British Thoracic Society guidance and agreed following clinician consultation. CAP admissions and individual organisational compliance with and impact of, CAP quality bundle measures was explored. Results: Average length of stay (LOS) was 10.4 days (median 6) 25% >13 days. Crude in‐hospital mortality rate was 17.6%, significantly lower (95% CI) than 19.1% in 2015/2016 and 19.3% in 2014/2015. Emergency readmissions within 28 days were 19.7% (19.2%; 2015/2016, 17.9%; 2014/2015). A total of 39.5% of patients received all appropriate care measures. Compliance has improved over time, although not for all hospitals. Most quality measures have higher mortality for those passing measures compared to those failing ( P < .05 95% CI). Giving oxygen, had a significantly higher emergency readmission rate, 3.3% higher (95% CI 1.1% to 5.5%). Appropriate antibiotics and recording CURB‐65 scores reduced the emergency readmission rates (−2.7% (95% CI −4.5% to −0.8%) −2.6% (95% CI −3.8% to −1.4%), respectively, ( P = ns)). Conclusion: CAP accounts for significant bed days, mortality and readmissions. Although mortality was lower, LOS and readmission rates were not, despite improvements in compliance after implementation of the care bundle. Care bundle use remained sub‐optimal.